Corruption crimes: problems of investigation and ways to solve them - Nikishkin A. V., Stepanov I. V., Soboleva P. S. (Economics and management: realias and prospects, 2019)
In the work the authors have comprehensively dealt with the investigation of crimes of corruption are problems faced by the investigation, in the process of consideration of this category of crimes
Keywords: corruption; правоохранительные органы; взяточничество; bribery; коррупционная деятельность; преступление; доказательства; взяткополучатель; предварительное расследование; crime; evidence; law enforcement; bribe taker; preliminary investigation